2014
DOI: 10.1080/13548506.2014.951367
|View full text |Cite
|
Sign up to set email alerts
|

Morningness/eveningness chronotype, poor sleep quality, and daytime sleepiness in relation to common mental disorders among Peruvian college students

Abstract: The study was designed to investigate the association between sleep disturbances and common mental disorders (CMDs) among Peruvian college students. A total of 2,538 undergraduate students completed a self-administered questionnaire to gather information about sleep characteristics, socio-demographic and lifestyle data. Evening chronotype, sleep quality, and daytime sleepiness were assessed using the Horne and Ostberg Morningess-Eveningeness Questionnaire (MEQ), Pittsburgh Sleep Quality Index (PSQI), and Epwor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 33 publications
(35 reference statements)
4
16
0
5
Order By: Relevance
“…No Quadro 1, as prevalências de TMC obtidas pelo GHQ-12 variaram de 18,5% a 48,7%, sendo inferiores a 20% em estudos realizados com alunos de medicina 39,40 , na Hungria. Identificou-se prevalências de 20 a 40% em cinco estudos, sendo três realizados em países desenvolvidos (enfermagem) [41][42][43] e dois em países em desenvolvimento (enfermagem e fisioterapia; e em outro não foi possível identificar a população) 44,45 . Outros cinco estudos, realizados em países desenvolvidos, encontraram prevalências superiores a 40% [46][47][48][49][50] .…”
Section: Resultsunclassified
“…No Quadro 1, as prevalências de TMC obtidas pelo GHQ-12 variaram de 18,5% a 48,7%, sendo inferiores a 20% em estudos realizados com alunos de medicina 39,40 , na Hungria. Identificou-se prevalências de 20 a 40% em cinco estudos, sendo três realizados em países desenvolvidos (enfermagem) [41][42][43] e dois em países em desenvolvimento (enfermagem e fisioterapia; e em outro não foi possível identificar a população) 44,45 . Outros cinco estudos, realizados em países desenvolvidos, encontraram prevalências superiores a 40% [46][47][48][49][50] .…”
Section: Resultsunclassified
“…Likewise, DSWP was defined by assessing bedtime and MEQ score. Sleep duration and delayed sleep phase are correlated [38]; however, a number of previous studies that evaluated the impact of late chronotypes did not consider sleep duration [3,39,40]. Therefore, we defined BIISS, DSWP, and BIISS + DSWP more strictly by following the aforementioned criteria in order to investigate the actual impact of insufficient sleep and delayed sleep-wake phase.…”
Section: Insomnia Insufficient Sleep and Delayed Sleep-wake Phase Inmentioning
confidence: 99%
“…In addition, an investigation of 2,538 students found that 33.4% of them had MCT, and female students were more likely to develop MCT (39.2%) than males (24.4%) 27 .…”
Section: Sleep Disorders and Anthropometric Measures In Chilean Univementioning
confidence: 99%